THE MYSTERY OF DREAMING AND REM SLEEP - Anton Coenen (MANASA, 2020)
Sleep is usually related to dreaming. However, it is still unknown why people dream and what is the importance of having a dream. This article will explore previous theories regarding dreaming and its association with REM sleep. The earliest research on sleeping and dreaming was marked by Eugene Aserinsky and professor Nathaniel Kleitman, which found a new stage of sleep called rapid eye movement or REM sleep. Then William Dement developed more research specifically in the field of dream observation. Both Aserinsky and Dement, along with Kleitman as their supervisor, became pioneers in sleep and dream studies. More studies were then developed with theory and hypothesis that tried to explain the mystery of dreaming, such as psychoanalytical dream theory and the activation – synthesis hypothesis. Despite both perspectives were opposed, those studies helped researcher in the field of dream to understand the relation between dreaming and REM sleep. Future research is needed in order to conduct a reliable interpretation of the manifest dream content and a stronger scientific basis in understanding the latent content of the dream.